Comparison of Serum Vitamin D Levels in Obese Subjects with and without Type 2 Diabetes Mellitus - Shen ZJ; Liu M; Zhang JX; Huang Y; Kong Y; Liu SG (Dove Medical Press, 2024)
Zhi-Jun Shen, Miao Liu, Jun-Xia Zhang, Yu Huang, Ying Kong, Shi-Guo Liu Department of Clinical Laboratory, Hubei Third People´s Hospital Affiliated to Jianghan University, Wuhan, 430033, People's Republic of ChinaCorrespondence: Shi-Guo Liu, Department of Clinical Laboratory, Hubei Third People´s Hospital Affiliated to Jianghan University, No. 26, Zhongshan Road, Wuhan, Qiaokou District, People's Republic of China, Email llsgg518@163.comBackground: Although observational studies have reported a correlation between vitamin D deficiency and type 2 diabetes mellitus (T2DM), epidemiological evidence on the risk of obese subjects suffering T2DM due to a vitamin D deficiency is limited. Therefore, we investigated the correlation between T2DM and serum vitamin D, lipids, blood pressure, insulin indexes in an obese population.Methods: A total of 1440 participants including 450 healthy controls and 990 obese subjects, 470 without T2DM and 520 with T2DM. Serum vitamin D levels were measured, and the association between low levels and T2DM in obese subjects was examined using multinomial and linear regression analyses.Results: Of the participants, 35% had deficient or insufficient vitamin D levels (ie, < 20 ng/mL). Compared with healthy controls, obese subjects, particularly those with T2DM had lower vitamin D levels. Multinomial logistic regression analysis showed that obese subjects with T2DM had a gradually increasing risk for desirable (RO = 1.41, 95% CI 1.06- 1.93, P = 0.027), insufficient (RO = 1.83, 95% CI 1.27- 2.84, P < 0.001), or deficient ((RO = 2.14, 95% CI 1.15- 3.75, P = 0.014) vitamin D levels. In obese subjects with T2DM, vitamin D levels correlated inversely with the risk indicators for diabetes, such as the levels of HbA1c (β = − 0.16, P = 0.002), fasting insulin (Fins; β = − 0.31, P = 0.008), and HOMA-IR (β = − 0.19, P < 0.001). In obese subjects without T2DM, vitamin D was associated negatively with the risk of having T2DM at five-year follow-up (relative risk = 0.93, 95% CI 0.79- 0.97, P = 0.037).Conclusion: This study demonstrates that low vitamin D levels correlate with the presence of T2DM in the obese population. This finding indicates that hypovitaminosis D may be a potential biological vulnerability factor for the development of T2DM in obese subjects.Keywords: vitamins, T2DM, obesity, biomarker